2013
DOI: 10.1007/s00704-013-0937-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Caspian Sea level using ECMWF seasonal forecasts and reanalysis

Abstract: The hydrological budget of the Caspian Sea (CS) is investigated using the European Centre for MediumRange Weather Forecasts interim reanalysis (ERAi) and seasonal forecast (FCST) data with the aim of predicting the Caspian Sea Level (CSL) some months ahead. Precipitation and evaporation are used. After precipitation events over the Volga River, the discharge (Volga River discharge (VRD)) follows with delays, which are parameterized. The components of the water budget from ERAi and FCSTs are integrated to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…We note that a previous study [Arpe et al, 2014] found good agreement between observed CSL change and ECM P-E flux estimates, plus Volga River R. In that study average annual PER flux was removed, including its mean value. The effect of this after integration over time would be to exclude linear trends, which are a dominant feature at longer time scales.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We note that a previous study [Arpe et al, 2014] found good agreement between observed CSL change and ECM P-E flux estimates, plus Volga River R. In that study average annual PER flux was removed, including its mean value. The effect of this after integration over time would be to exclude linear trends, which are a dominant feature at longer time scales.…”
Section: Conclusion and Discussionmentioning
confidence: 53%
“…The effect of this after integration over time would be to exclude linear trends, which are a dominant feature at longer time scales. Removing PER flux means (or using PER flux anomalies) appears to be a valid approach when focusing in nonlinear CSL changes [Arpe et al, 2014]. If the PER flux mean was not removed, the PER-predicted, long-term CSL changes (based on ECM P-E, plus Volga River R) would be significantly larger than those observed.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In 1995, the CSL reached its peak. Before that year the Volga had excessive precipitation and after that reduced precipitation (Arpe et al , , ). The direct connection between T2m and ENSO is weak.…”
Section: Discussionmentioning
confidence: 99%
“…The NAO, EA and SCA indices in this study are defined as standardized first, second and third principal component time series calculated from seasonal-mean SLP anomalies in the region [70 W-60 E, 20 -80 N], which includes the CS basin. We focus on the winter season, Dec-Jan-Feb (DJF), as the NAO and other modes display their largest climate impact in the boreal winter months (Arpe et al, 2000;Arpe et al, 2014;Hurrell et al, 2003;Hurrell et al, 2013). All data was detrended before performing the EOF analysis.…”
Section: Climate Indicesmentioning
confidence: 99%